SPEECH DELAY IN CHILDREN: UNRAVELING THE ROLES OF FRAGMENTED FAMILY, INADEQUATE CAREGIVER, AND EXCESSIVE PHONE USAGE – CASE REPORT - Gizta, Aura Bella; Sururi, Desy Aulina; Wahyuningtyas, Mariana; Arsini, Putu Sudewi; Putri, Winarni Dian Dwiastuti Wisnu (Journal of Psychiatry Psychology and Behavioral Research, 2026)
Introduction: This article discusses the risk factors for speech delay, a communication development disorder, specifically the development of speech and language in children. Communication disorders can disrupt motor and cognitive development. Risk factor detection is necessary to prevent speech delay and ensure that the treatment is suitable. Methods: This study employed a qualitative descriptive research design using a case study approach. Data collection techniques included observation, interviews, and documentation. The case study involved one subject, a 47-month-old male child. Qualitative data analysis techniques were conducted using the Miles and Huberman model. Results: Signs and symptoms of speech delay in N were already shown at the age of 24 months, and the definitive diagnosis was made at the age of 32 months. More than one non-medical risk factor was found, including a fragmented family, an inadequate caregiver, and excessive phone usage. The therapy provided was a combination of speech therapy with visual aids, actively reading stories from books, and fulfilling social interaction needs. Discuss: Child development milestones should always be monitored to identify signs and symptoms of speech delay. Kuesioner Pra-Skrining Perkembangan [KPSP] screening can be used for early detection of child development disorders. The therapy implemented should be followed up to ensure progress in speech and language development. Conclusion: N's speech delay is caused by a fragmented family, inadequate caregiver, and excessive phone usage. We provide support to parents/caregivers. We also recommend following up on the monitoring of N’s speech and language development progress.  Keywords: speech delay, communication, phone usage.